Electrocatalytic nanostructured ferric tannate as platform for enzyme conjugation: Electrochemical determination of phenolic compounds - Magro, Massimiliano; Baratella, Davide; Colò, Veronica; Vallese, Francesca; Nicoletto, Carlo; Santagata, Silvia; Sambo, Paolo; Molinari, Simone; Salviulo, Gabriella; Venerando, Andrea; Basso, Caroline R. [UNESP]; Pedrosa, Valber A. [UNESP]; et al. (Elsevier, 2020)
A shell of nanostructured ferric tannates was spontaneously developed on the surface of naked maghemite nanoparticles (SAMNs, the core) by a simple wet reaction with tannic acid (TA). The as obtained core–shell nanomaterial (SAMN@TA) displays specific electrocatalytic and surface properties, which significantly differ from parent maghemite. Thanks to the known proclivity of TA to interact with proteins, SAMN@TA was proposed as a support for the direct immobilization of an enzyme. A ternary functional nanobioconjugate (SAMN@TA@TvL) was successfully self-assembled by incubating laccase from Trametes versicolor (TvL) and SAMN@TA. The SAMN@TA@TvL hybrid was kinetically characterized with respect to the native enzyme and applied for building an easy-to-use analytical device for the detection of polyphenols. The electrochemical biosensor allowed the determination of polyphenols by square wave voltammetry in mixed water-methanol solutions. The system sensitivity was 868.9 ± 1.9nA µM−1, the LOD was 81 nM and the linearity range was comprised between 100 nM and 10 µM. The proposed approach was successfully applied to detect phenolics in blueberry extracts as real samples. Results suggest that SAMN@TA could be a promising, low cost and versatile tool for the creation of nano-bio-conjugates aimed at the development of new electrochemical sensing platforms.
Keywords: Biosensor; Enzyme immobilization; Hybrid nanomaterials; Laccase; Magnetic nanoparticles; Phenolic determination; Tannic acid